Penggunaan Media Flashcard dan Materi dari Situs A Cup of French dalam Pembelajaran Menulis Kalimat Sederhana Bahasa Perancis - Karimah, Iim Siti; Sopiawati, Iis; Maghfira, Zakkisani (Universitas Muria Kudus, 2025)
This study aims to: 1) outline the steps for integrating flashcards and materials from the A Cup of French website into teaching students how to write simple French sentences; 2) assess students's proficiency in writing simple French sentences pre and post using these resources; and 3) explore students's feedback on using these resources. The research utilized a pre-experimental approach with a One-Group Pretest and Posttest Design, employing tests and questionnaires as instruments. The sample comprised 24 students from a vocational high school (SMKN) in Bandung. The study identified the following steps for utilizing flashcards and A Cup of French materials: 1) presenting and explaining the learning material; 2) allowing students to pick shuffled flashcards related to the material; 3) having students write simple French sentences based on the flashcards in their notebooks; 4) giving students each turns to write their answers on the board; and 5) correcting any mistakes or inaccuracies. Data analysis revealed that the average pretest score was 81.6%, while the posttest average increased to 93.1%, reflecting an improvement of 11.5%. These results fall into the